FISIOTERAPI KOMUNITAS DALAM PENCEGAHAN RISIKO VASCULAR DISEASE DI KLUB JANTUNG SEHAT LESTARI RW 015 KELURAHAN JATISAMPURNA - Achirda, Nur; Abida, Liza Laela; Anggraeni, Assyifa Fitri; layyina, Fatimah zahra nur; Khairunisa, Millenia; Fahreza, Robby Daniel (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Background: Cardiovascular disease is a disease that attacks the body's cardiovascular system including the heart and blood vessels. One of the cardiovascular diseases is stroke. The importance of physical activity and education can increase awareness of body health and knowledge about stroke and vascular disease prevention. This can have a positive effect in maximizing the body's recovery optimally. Purpose: This community physiotherapy aims to determine the level of knowledge of the community at the Sustainable Heart Club regarding Vascular Disease. Methods: Community physiotherapy activities are carried out in 4 activities, namely problem identification, identification of intervention solutions, provision of interventions and prevention of potential problems. Results: There was a significant increase in the level of knowledge of respondents regarding stroke and vascular disease and their prevention. Conclusion: Aerobic exercise and providing education related to preventing the risk of vascular disease can have a positive effect on society. Keywords: Elderly, cardiovascular disease, stroke, physical activity, education